Clinical activity of the mutant-selective EGFR inhibitor AZD9291 in patients with EGFR inhibitor—resistant non-small cell lung cancer - Jiang, Tao (Transl Lung Cancer Res, 2014)
The first generation epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) are effective in advanced non-small cell lung cancer (NSCLC) with EGFR mutations. Unfortunately, disease progression generally occurs after 9 to 14 months of targeted therapy. The substitution of threonine with methionine at amino acid position 790 (T790M), as the second mutation in EGFR, is the most common resistance mechanism and is detected in tumor cells from more than 50-60% of patients after disease progression. However, current targeted therapeutic strategies for patients with acquired resistance are limited. This has led to the development of “third generation” EGFR-TKIs that are designed to target T790M and EGFR-TKI sensitizing mutations more selectively than wild-type. AZD9291, as a mono-anilino-pyrimidine compound, is a novel, irreversible EGFR-TKI, has proved to be more effective against both EGFR-TKI sensitizing and resistance T790M mutations in preclinical models. This phase I clinical study showed that AZD9291 has robust efficacy and is well tolerated in EGFR mutant NSCLC patients with acquired resistance to EGFR-TKIs.